CULTURAL COMMUNICATION THROUGH THE RAMPAK GENTENG ART FORM AS A LOCAL IDENTITY OF JATIWANGI - Azhar Maulidani; Khaerudin Imawan; Aghnia Dian Lestari (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2026)
Sustainability of local cultures is threatened by globalization and popular culture, including a drop in public interest in traditional arts. A similar phenomenon can be observed in the Jatiwangi community, which has long been involved in the clay roof-tile industry. The community, however, is working to retain its cultural identity with the help of an art form called Rampak Genteng, in which they perform together. This study is designed to examine the role of the community in building and strengthening local cultural identity, analyze Rampak Genteng which is a practice of cultural communication and understand the symbolism of the roof tiles. The approach of this research is qualitative in which the ethnography of communication approach is applied to the theory of Dell Hymes and in-depth interview and observation techniques are used as data collection methods. The findings indicate that Rampak Genteng is a cultural communication event that contains the elements of SPEAKING: setting and scene, participants, ends, act sequence, key, instrumentalities, norms and genre where the social interaction, cultural symbols, and community participation are structured as a communication system. Not only are the roof tiles instruments of music, but they're also a representation of local identity and pride. Moreover, the involvement of the community is evident, indicating that this art form is used as a tool for preserving the culture, thereby creating a sense of community identity. Rampak Genteng is therefore not only a form of art, it also serves as a means of cultural communication and contributes to the maintenance of the sustainability of the local identity in the face of globalization.